2021
DOI: 10.3389/fneur.2021.635894
|View full text |Cite
|
Sign up to set email alerts
|

Parents and Caregivers Satisfaction After Palliative Treatment of Spastic Hip Dislocation in Cerebral Palsy

Abstract: Objectives: Pain appearance is one the most common complication of spastic hip disease in children with cerebral palsy (CP). It determines child and caregiver quality of life and life priorities. Reconstruction hip surgery should be considered as a treatment of choice. Some clinical conditions give the inability to perform such a procedure. In our paper, we would like to present four palliative methods of spastic hip dislocation treatment in children with CP.Material: We analyzed four groups of patients treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…There are few comparative studies and follow-up has generally been short- to medium-term. The majority of studies lack adequate documentation of pain before and after surgery as well as valid patient reported outcome measures (PROMS) [ 43 , 77 , 78 , 79 , 80 ]. A notable exception was the study by Koch et al [ 79 ].…”
Section: Palliation Of Cphd and The Role Of Salvage Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…There are few comparative studies and follow-up has generally been short- to medium-term. The majority of studies lack adequate documentation of pain before and after surgery as well as valid patient reported outcome measures (PROMS) [ 43 , 77 , 78 , 79 , 80 ]. A notable exception was the study by Koch et al [ 79 ].…”
Section: Palliation Of Cphd and The Role Of Salvage Surgerymentioning
confidence: 99%
“…The majority of studies lack adequate documentation of pain before and after surgery as well as valid patient reported outcome measures (PROMS) [ 43 , 77 , 78 , 79 , 80 ]. A notable exception was the study by Koch et al [ 79 ]. They compared the outcomes of three surgical groups to injection of the painful hip with local anaesthetic and corticosteroid.…”
Section: Palliation Of Cphd and The Role Of Salvage Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, so far only one retrospective study [ 33 ] has investigated the effectiveness of an IACI in 15 children with neurologic HD. It showed that injections of betamethasone reduced pain and improved parents’ and caregivers’ satisfaction, with a benefit lasting an average of 4 months but decreasing during follow up.…”
Section: Introductionmentioning
confidence: 99%
“…One must understand the social situation at home. Does the family appreciate the complexity and intensity of the surgery? 4 Do they own their own home, rent an apartment, struggle with accommodation, etc.? Are they on the ground floor or on the top floor with (or without) an elevator?…”
mentioning
confidence: 99%